Guidelines for de novo phasing using multiple small‐wedge data collection. Corrigendum. (15th February 2022) - Baba, Seiki; Matsuura, Hiroaki; Kawamura, Takashi; Sakai, Naoki; Nakamura, Yuki; Kawano, Yoshiaki; Mizuno, Nobuhiro; Kumasaka, Takashi; Yamamoto, Masaki; Hirata, Kunio
Abstract : A figure in the article by Baba et al. [(2021), J. Synchrotron Rad. 28, 1284–1295 ] is corrected. Abstract : A figure in the article by Baba et al. [(2021), J. Synchrotron Rad. 28, 1284–1295 ] is corrected.